Case Study of the Singapore Prison Service Strategic Transformation : A Bold Step Towards Excellence - LIM, Beng Wee (2006)
Singapore Prison Service (SPS) operates under the framework of the Singapore government's criminal justice system (CJS) to uphold law and order in the society to provide a safe and secure environment.